Fabrication and Performance Evaluation of Multi-Cell Arrayed Planar SOFC Stack - Kim, H.; Jung, H. Y.; Jung, H. -G.; Kim, J.; Lee, J. -H.; Lee, H. -W.; Song, H. (SOLID OXIDE FUEL CELLS 10 (SOFC-X), PTS 1 AND 2, 2007)
SOFC technology has been developed in order to accomplish high power capacity system and satisfy economic requirements. We have been developing anode supported planar SOFCs with large active area by employing various multi-cell arrays and compressive sealing system. The 4-cell and 2-cell array systems, which were equivalent to 10 cm x 10 cm unit cell in active area, were operated successfully to achieve high power density of 0.46 W/cm(2) and 0.45 W/cm(2) at 750 degrees C respectively. By means of enhanced compressive sealant, this equivalent cell system was assembled without any aid of auxiliary anchoring parts. Our results provide a feasible alternative for realization of planar SOFCs of high power capacity by increasing active area with currently available fabrication techniques.